KARAKTERISTIK PASIEN PREEKLAMPSIA DI RUMAH SAKIT UMUM DAERAH SOEDIRAN MANGUN SOEMARSO WONOGIRI JAWA TENGAH - Weningtyas, Vyanda Sri; Adnan, Muhammad Luthfi; Pramaningtyas, Miranti Dewi; Wahyana, Eka Budi (Inisiasi, 2024)
Preeclampsia is a condition of increased blood pressure accompanied by proteinuria during pregnancy. Preeclampsia is one of the causes of maternal and fetal death. Efforts to reduce the incidence of preeclampsia are one of the efforts to reduce maternal mortality, one of which is by knowing the characteristics of preeclampsia patients to plan to overcome the risk of preeclampsia in the future. This study aims to determine the characteristics of preeclampsia patients at Wonogiri Regional Hospital dr. Soediran Mangun Soemarso, Wonogiri, Central Java. This research was conducted in a retrospective cross-sectional manner on the medical records of preeclampsia patients in Wonogiri Regional Hospital dr. Soediran Mangun Soemarso, Wonogiri, Central Java during 2019-2022. Sampling was carried out using a purposive sampling method among pregnant women who gave birth in the hospital from November 2021 – Januari 2022. A total of 106 medical record data from pregnant women were obtained in this study. The average age of pregnant women in this study was 31.37 ± 6.72 years with the majority aged 20 – 35 years with a history of giving birth more than twice. The majority of preeclampsia patients at Wonogiri Regional Hospital were severe preeclampsia patients (53.8%). A total of 59 pregnant women gave birth using the vaginal delivery method and 47 pregnant women gave birth using the cesarean method.   Maternal age and pregnancy history are factors related to the risk of preeclampsia which can influence the mother's delivery method. Further research is needed on risk factors for preeclampsia in a wider population so as to improve the health of mothers and babies during pregnancy